On-line measurement of battery impedance using motor controller excitation - Howey, D; Mitcheson, P; Yufit, V; Offer, G; Brandon, N (Institute of Electrical and Electronics Engineers, 2013)
This paper presents a fast, cost effective technique for the measurement of battery impedance on-line in an application such as an electric or hybrid vehicle. Impedance measurements on lithium-ion batteries between 1 Hz and 2 kHz give information about the electrochemical reactions within a cell, which relates to state of charge, internal temperature and state of health. We concentrate on the development of a measurement system for impedance that for the first time uses an excitation current generated by a motor controller. Using simple electronics to amplify and filter the voltage and current, we demonstrate accurate impedance measurements obtained with both multisine and noise excitation signals, achieving RMS magnitude measurement uncertainties between 1.9% and 5.8% in comparison to a high accuracy laboratory impedance analyser. Achieving this requires calibration of the measurement circuits, including measurement of the inductance of the current sense resistor. A statistical correlation approach is used to extract the impedance information from the measured voltage and current signals in the presence of noise, allowing a wide range of excitation signals to be used. Finally, we also discuss the implementation challenges of a state of charge estimation system based on impedance.